Psikologi Organisasi dalam Manajemen Pendidikan: Kajian Kejiwaan, Proses Belajar-Mengajar, dan Perspektif Hadits - Kurniawati, Eti; Patmawati, Tia (CV. Kalimasada Group, 2024)
This study discusses the relationship between organizational psychology and psychological aspects in the teaching and learning process, with a focus on the study of theory and hadith. In the context of education, understanding the psychological dynamics of both teachers and students is essential to create an effective learning environment. Organizational psychology provides insight into how structure, culture, and interactions within an educational institution can affect an individual's motivation and performance. In addition, psychological aspects such as emotions, stress, and interpersonal relationships are key factors in the teaching and learning process. Because these things can affect motivation, activities, and creativity which are very important in the teaching and learning process, this study examines various relevant psychological theories, and relates them to the teachings of hadith which is the main reference after the Qur'an for Muslims. With this multidisciplinary approach, it is hoped that more effective strategies can be found to improve the quality of the teaching and learning process, as well as contribute to the development of better educational institutions. This research is expected to be a foundation for educators and managers of educational institutions in applying the principles of psychology to create a more supportive and productive learning environment.